SOCIAL AND PEDAGOGICAL FORECASTING IN THE PROCESS OF CHILDREN’S SOCIALIZATION - Antonina L. Leutina (Образование и наука)
An increase in the importance of prediction in pedagogic activity is related to modern postindustrial economic trends which are becoming oriented primarily toward an individual and his/her personal abilities as a basic manufacturing resource. The increase in personal resource value determines the application of socio-structural approach in pedagogy which contributes to the reduction of risks connected with the results of pedagogic activity and makes prediction of social and personal evolution of a child more prominent. The aim of the present research is to provide an analysis of prevalence of predictive thinking in modern theoretic pedagogy as well as elaboration of methodological schemes of implementation of social and pedagogic prediction in pedagogic activity, the primary function of which is successful socialization of children. Methods. The content-analysis of results of the researches published in scientific and pedagogical journals during 2006–2013, has shown that in modern educational practice while implementing the measures on children socialization, projective technologies of forecasting of the future of pupils are used precious little or are not used at all. The socio-constructive approach reducing many risks of pedagogical activity is given; as an effective toolkit of prospects determination of social and personal development of the child. Results. The author draws readers’ attention to the advantages of the organisation of the educational process based on a teacher’s reflection of achievements and abilities of the pupil, and prolonged forecasting on the ground of possible ways of the further students’ personality development. Scientific novelty. The author is the first to introduce the ontological socialization scheme and the scheme of socialization process as a natural and artificial system based on positions of the concept of socio-technical systems management developed by the founder of the Moscow methodological coterie, G. P. Schedrovitskij. The necessity of using in pedagogy of two types of prediction – «pedagogic» and «social» is proved in the article on the grounds of the schemes presented by the author. Practical significance. The methods of forecasting activity proposed in the research will help teachers-experts to organise their professional work in a more effective, rational and qualitative way.